Effect of polymerization techniques and cleaning solution on flexural resistance of acrylic resin chemically activated - Oliveira, Derly Tescaro Narcizo de; Almeida, Margarete Teresa Gottrardo de; Rezende, Maria Cristina Rosifini Alves [UNESP]; Bertoz, André Pinheiro de Magalhães [UNESP]; Bigliazzi, Renato [UNESP]; Bertoz, Francisco Antônio [UNESP] (My University, 2015)
The purpose of this study was to evaluate the impact of different disinfection solutions on flexural resistance of chemically-activated acrylic resin. Test pieces were made of clear acrylic resin using a rectangular mold and employing two techniques: wet polymerization under pressure (n = 20) and dry polymerization under pressure (n = 20). Test pieces were subdivided into four equal groups: distilled water (control), sodium bicarbonate, 1% sodium hypochlorite and effervescent ats. The 30-day cycling technique consisted of immersing the test pieces in 100 ml of solution for 10 min three times a day and placing them in closed containers containing artificial saliva at 37°C. Subsequently, the flexural resistance of samples was tested. Data were analyzed using two-way analysis of variance (ANOVA) with forces serving as the dependent variables and the polymerization technique and cleaning agents as independent variables. Post hoc multiple comparisons were performed using Tukey’s test. There was no statistically significant difference in the flexural strength between the two polymerization techniques. The greatest flexural strength was observed for the effervescent tablets group followed by the control and 1% sodium hypochlorite groups which were statistically similar. Thus, the sodium bicarbonate solution caused the lowest flexural resistance of the test pieces.
Keywords: Polymethyl methacrylate; Material resistance; Disinfection; Orthodontic appliances